2012
DOI: 10.1007/s12402-012-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

PPP2R2C as a candidate gene of a temperament and character trait-based endophenotype of ADHD

Abstract: There are several lines of evidence that the 4p16 region is a candidate locus of both attention-deficit/hyperactivity disorder (ADHD) and bipolar disorder. None of the harbored candidate genes of this region were hitherto shown to be associated with ADHD despite promising functionality. One of the most promising candidate genes in this region is protein phosphatase 2, regulatory subunit B, gamma (PPP2R2C), which, however, thus far has not been assessed for a potential association with ADHD. A total of 513 in- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…These are showed in Supplementary Table 1. 35, 48, 53, 54, 57, 60, 64, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113 In particular, among the most known, DRD5 , whose highly polymorphic dinucleotide repeat (CA) n has been the most studied in adults, three studies 54, 60, 80 were available, but Squassina et al 80 was excluded because no frequencies were reported. Ribases et al 48 investigated other polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These are showed in Supplementary Table 1. 35, 48, 53, 54, 57, 60, 64, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113 In particular, among the most known, DRD5 , whose highly polymorphic dinucleotide repeat (CA) n has been the most studied in adults, three studies 54, 60, 80 were available, but Squassina et al 80 was excluded because no frequencies were reported. Ribases et al 48 investigated other polymorphisms.…”
Section: Resultsmentioning
confidence: 99%
“…Other genes were studied in single studies: for instance circadian locomotor output cycles kaput (CLOCK), 105 protein kinase G ( PRKG1 ), 106 mineralocorticoid receptor ( NR3C2 ), 107 CKLF-like MARVEL transmembrane domain containing 8 ( CMTM8 )/diacylglycerol kinase eta ( DGKH )/neuronal PAS domain protein 3 ( NPAS3 )/solute carrier family 39 (zinc transporter), member 3 ( SLC39A3 )/deafness, autosomal recessive 31 ( DFNB31 )/epidermal growth factor receptor ( EGFR ), 108 neural cell adhesion molecule 1 ( NCAM1 )/tetratricopeptide repeat domain 12 ( TTC12 )/ankyrin repeat and kinase domain containing 1 ( ANKK1 ), 82 Ca(2+)-binding extracellular heparan/chondroitin sulfate proteoglycan ( SPOCK3 ), 109 disrupted in schizophrenia 1 ( DISC1 ), 110 Kv channel-interacting protein 4 ( KCNIP4 ), 111 phosphatase 2, regulatory subunit B, gamma ( PPP2R2C ), 112 forkhead box P2 ( FOXP2 ), 113 αN-catenin protein (CTNNA2), 96 u-opioid receptor (OPRM1), and others. 60 Thus we did not perform meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with our results, which demonstrate that the expression of the PPP2R2C gene was enriched in the human brain, a previous study on the mouse brain has suggested that the expression of the PPP2R2C gene may play a role in synaptic plasticity 19 . In addition, a preliminary report indicates that the PPP2R2C gene could increase vulnerability for attention-deficit/hyperactivity disorder (ADHD) 20 . Moreover, dysregulation of other B regulatory subunits of PP2A, which modulate tau phosphorylation, have been implicated in neurodegenerative disorders such as Alzheimer’s disease 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…In cultured cells, PPP2R2C expression regulates PP2A activity and tau dephosphorylation. These results suggest that dysregulation of PPP2R2C expression may be involved in the onset of AD and that specifically targeting PPP2R2C expression or activity is a promising strategy against brain dementia disorders, including AD and other tauopathies [10][11][12][13].…”
Section: Introductionmentioning
confidence: 92%